Biomechanics of axial load transmission across the native human elbow. (October 2021) - Smithson, Kaleb; Smith, Jacob; Hogue, William; Mannen, Erin; Ahmadi, Shahryar
Background: Elbow and forearm motion are thought to affect elbow load transmission, yet little empirical evidence exists to quantify the biomechanics. Methods: Eight fresh-frozen human cadaver upper extremities were utilized. A 100 N axial force was applied across the elbow joint at elbow flexion angles of (0°, 30°, 60°, and 90°) and forearm rotation angles (0°, 45° supination, and 45° pronation). Pressure mapping sensors were placed in both the radiocapitellar and ulnotrochlear joints. Force distributions and contact areas were measured, and paired t-tests were used for comparison (p < 0.05). Results: The average maximum loading percentage of the radiocapitellar and ulnotrochlear joint pressures were 57.8 ± 4.6% and 42.2 ± 4.6%, respectively. Elbow flexion angle and forearm rotation did not significantly affect the joint loading. There was no significant difference between the contact areas of each joint, although ulnotrochlear and radiocapitellar joints demonstrated an inverse relationship. Conclusion: Our study is the only one to date to comprehensively evaluate loading mechanics throughout both functional elbow flexion and forearm rotation across both articulations. The load sharing ratio across the radiocapitellar and ulnotrochlear joints was 58%:42%, agreeing with previously reported ratios with limited parameters. A relationship may be present between increasing radiocapitellar and decreasing ulnotrochlear contact areas as elbow flexion increases.